Isolation of Salmonella species of public health concern from commonly fed dried meat dog treats. (30th January 2023) - Morgan, Genever; Saal, Mikhela; Corr, Aoife; Jenkins, Claire; Chattaway, Marie Anne; Pinchbeck, Gina; Williams, Nicola
Abstract: Background: Dried non‐heat‐treated meat treats, such as ears, skin and tails, are popular supplementary dog foods. Previous studies have demonstrated Salmonella spp. contamination on treats, particularly in pig ears and chicken products. This small, exploratory, cross‐sectional study investigated Salmonella spp. presence in dried treats available in the UK. Methods: A selection of dried treats from local pet shops and online retailers underwent bacterial culture for Salmonella spp. and subsequent antimicrobial susceptibility testing, with Salmonella serotype determined by whole genome sequencing. Results: Eighty‐four samples were tested, with 16% being Salmonella spp. positive. Five Salmonella serotypes were identified, each associated with specific treat types. An antimicrobial‐resistant phenotype was identified in 39% of isolates. All serotypes identified are known to cause human infection. Limitations: This study was limited by a small sample size and limited number of retail sources. Conclusion: Salmonella spp. of public health concern were present in some dried dog treats in this study. Dog owners, pet food retailers and veterinary professionals should be aware of the potential zoonotic disease risk associated with these treats, and appropriate hygiene measures, including thorough hand washing, should be utilised if they are fed.